Farmers' Knowledge of Handling and Preventing Emergencies in Agricultural Areas - Safa Tri Wulandari; Futuwwah Sotya Cahyani; Gipsy Rayhan Ghafur; Enggal Hadi Kurniyawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan; Robby Prihadi Aulia Erlando; Rany Agustin Wulandari (KHD Production, 2024)
The incidence of work accidents in agricultural areas is quite a lot such as pesticide exposure incidents, exposure to sharp agricultural machinery or equipment, animals and plants that can injure, and positions that are not ergonomic so that it requires immediate handling. This study aims to analyze farmers' knowledge about handling and preventing emergencies in agricultural areas. This study uses the literature review method using 3 databases, namely Google Scholar, Science Direct and PubMed by considering the publication time span for the last five years, from 2020 to 2024. We used 10 studies that met the inclusion criteria in the review. It was found that some farmers have knowledge about the attitude and ability to handle emergencies. Some farmers have good knowledge, but their attitudes and knowledge related to handling emergencies are still quite low. Low knowledge and attitude towards handling emergencies can lead to undesirable outcomes such as death or long-lasting physical disability. Farmers' knowledge is also important to reduce the risk of work accidents in agricultural areas. Factors that cause a lack of knowledge and attitudes related to handling emergencies are the lack of awareness of farmers and the attitude of farmers who are too indifferent to work accidents, as well as the lack of education and training related to handling or first aid related to work accidents. For this reason, support from the government and health workers is needed to provide education and training to improve farmers' knowledge.